Dolos and Dikê in Sophokles' Elektra - MacLeod, Leona. (Mnemosyne, Supplements, 2001)
The main problem facing critics of Sophokles' Elektra has always been understanding the presentation of the vengeance and the nature of justice it represents. This volume addresses the ethical issues of this play through an analysis of the language and argumentation which the characters use to explain and justify their behaviour. The focus is on the examination of the themes of aidôs and dolos , and the way in which each contributes to our overall understanding of the vengeance as an act which, for all its justice, remains shameful. By exploring the union between these two contradictory elements, this study exposes the ethical complexity of Sophokles' treatment of the vengeance theme. Dolos andamp; Dikê contains a useful critique of recent interpretative approaches to the play, a full bibliography, and a complete index of passages cited.